Systematizing the Instruments of Trade Wars and of Concealed Protectionism - Serpukhov Maksym Yu.; Mazorenko Oksana V. (Bìznes Inform, 2017)
The article is concerned with the problems of trade wars and hidden protectionism in the process of implementing international trade. The main purpose of the research is systematization of trade barriers and instruments used in the trade wars between countries. The basic instruments of trade wars have been analyzed, a list of the key instruments used in the trade wars between countries has been defined, and also the possible influence of these instruments has been described. The statistical analysis has resulted in identifying the main trade barriers and the most popular sectors of the economy in which protectionism instruments are applied. The authors have also defined the main interventions applied by different world countries in relation to Ukrainian products and groups of Ukrainian goods to which the most restrictions by the world countries are applied. The conclusions on counteraction and adaptation to the most popular instruments of protectionism in the process of activation of the export activity of country have been generalized.